Development of DINA character-based materials to improve Pancasila learning outcomes - Susanna Br. Ginting; Reh Bungana Br. Perangin-angin; Wildansyah Lubis (Inovasi Kurikulum, 2025)
The low level of student engagement in learning and the dominant use of lecture and memorization methods, which are less effective in shaping students' understanding and character, are the background to this research. This research aims to develop DINA character-based Pancasila Education teaching materials in Christianity to improve the learning outcomes of second-grade elementary school students on the theme of environmental care. This research uses the Research and Development (RnD) method with a 4D development model approach, which consists of the stages of define, design, develop, and disseminate. Data collection instruments include observation, interviews, tests, and validation questionnaires, which are developed by experts, comprising design experts, linguists, and material experts. The validation results indicate that the developed teaching materials are highly suitable for use in learning, as they meet the eligibility criteria from various aspects. The practicality of the teaching materials is also evident through positive responses from students and teachers, who find the materials interesting, easy to use, and relevant to everyday life. The effectiveness of the teaching materials is demonstrated by an increase in students' ability to understand the material, as well as positive changes in their attitudes and behaviors regarding environmental care that align with DINA character values, such as responsibility, simplicity, and sincerity. Learning becomes more enjoyable and contextual through the integration of visuals, stories, and exploratory activities. This study recommends that the development of character-based teaching materials, such as DINA, be continued and implemented in other subjects to strengthen character education from an early age.   Abstrak Rendahnya keterlibatan peserta didik dalam pembelajaran serta dominannya penggunaan metode ceramah dan hafalan yang kurang efektif dalam membentuk pemahaman dan karakter peserta didik menjadi latar belakang dilakukannya penelitian ini. Penelitian ini bertujuan untuk mengembangkan bahan ajar Pendidikan Pancasila berbasis karakter DINA dalam Katolik guna meningkatkan hasil belajar peserta didik kelas II SD pada tema peduli lingkungan. Penelitian ini menggunakan metode Research and Development (RnD) dengan pendekatan model pengembangan 4D, yang terdiri dari tahapan define, design, develop, dan disseminate. Instrumen pengumpulan data mencakup observasi, wawancara, tes, serta angket validasi oleh para ahli yang terdiri atas ahli desain, ahli bahasa, dan ahli materi. Hasil validasi menunjukkan bahwa bahan ajar yang dikembangkan sangat layak digunakan dalam pembelajaran karena memenuhi kriteria kelayakan dari berbagai aspek. Kepraktisan bahan ajar juga diperoleh melalui tanggapan positif peserta didik dan guru yang menilai bahan ajar menarik, mudah digunakan, serta relevan dengan kehidupan sehari-hari. Efektivitas bahan ajar ditunjukkan melalui peningkatan kemampuan peserta didik dalam memahami materi, serta adanya perubahan positif dalam sikap dan perilaku peduli lingkungan yang sejalan dengan nilai-nilai karakter DINA seperti tanggung jawab, kesederhanaan, dan ketulusan. Pembelajaran menjadi lebih menyenangkan dan kontekstual melalui integrasi visual, cerita, dan aktivitas eksploratif. Penelitian ini merekomendasikan agar pengembangan bahan ajar berbasis karakter seperti DINA terus dilakukan dan diterapkan dalam mata pelajaran lain untuk memperkuat pendidikan karakter sejak dini. Kata Kunci: bahan ajar; hasil belajar; karakter DINA; peduli lingkungan; pendidikan Pancasila